Pengembangan Wisata Kolam Pemancingan Temenggung untuk Meningkatkan Taraf Kehidupan Masyarakat Desa Balonggebang - Gatutkoco Hangger Prebowo Wibisono; Alif Valentino Briliyan; Sindy Triana Putri; Crysanti Chandra Asia; Taufikur Rahman (Universitas 17 Agustus 1945 Semarang, 2023)
Nganjuk Regency's location in the middle of Java makes it difficult for its people to enjoy marine products, so freshwater fish is the solution for its residents. No wonder there are so many fishing ponds in the district, especially in Balonggebang Village. This condition has become a special attraction in Balonggebang Village, making it one of the village's tourism potentials. Kedungrejo Hamlet is one of the hamlets that has a fishing pond. The development of the fishing area aims to improve the standard of living of the village community. This service activity uses data collection and area design. The design of the fishing area was welcomed by the Village Government because later it could make Balonggebang Village develop well.